Indonesian Islam: History, Characteristics and Global Contribution - Abon Ronaldi; Arief Subhan; Arif Zamhari (Fakultas Ushuluddin, Adab dan Humaniora (FUAH) UIN Kiai Haji Achmad Siddiq Jember, 2023)
Abstract: Indonesia is the largest democracy in the world, as well as the country with the most followers of Islam. Orientalists consider Islam in Indonesia as Islam that departs from principles that are different from Islam in the Middle East. The persuasive style of Indonesian Islam is due to the process of Islamization that has been carried out. The process of Islamization in the archipelago merged with the local culture. In contrast to the process of Islamization in the Middle East which was dominated by military action. By analyzing various sources, this study concludes that Indonesian Islam is able to contribute to the global world. Indonesian Islam provides an example of the practice of religious pluralism and democracy that go hand in hand. This is because Indonesia made the legality of several religions. In the end, it gave birth to the term Islam Wasatiyah which is the result of the integration of Indonesian Islamic culture. This Islamic movement was initiated by a large Islamic organization in Indonesia. And continue to be introduced in the global realm as a contribution to world civilization.